Effects of Maturity and Processing on the Volatile Components, Phytochemical Profiles and Antioxidant Activity of Lotus (Nelumbo nucifera) Leaf - Zhili Ma; Yu Ma; Yin Liu; Bei Zhou; Yalin Zhao; Ping Wu; Dexin Zhang; Deyuan Li (Foods, 2023)
In this study, fresh lotus leaves at two maturity stages were processed to tea products by different methods (white-tea process, green-tea process and black-tea process). The volatile compounds, phytochemical profiles and antioxidant activities of lotus-leaf tea were investigated. A total of 81 volatile components were identified with HS-GC-IMS. The mature lotus-leaf tea showed more volatile compounds than the tender lotus-leaf tea. The lotus leaf treated with the white-tea process had more aroma components than other processing methods. In addition, six types of phenolic compounds, including luteolin, catechin, quercetin, orientin, hyperoside and rutin were identified in the lotus-leaf tea. The mature leaves treated with the green-tea process had the highest levels of TPC (49.97 mg gallic acid/g tea) and TFC (73.43 mg rutin/g tea). The aqueous extract of lotus-leaf tea showed positive scavenging capacities of DPPH and ABTS radicals, and ferric ion reducing power, whereas tender lotus leaf treated with the green-tea process exhibited the strongest antioxidant activity. What is more, the antioxidant activities had a significant positive correlation with the levels of TPC and TFC in lotus-leaf tea. Our results provide a theoretical basis for the manufacture of lotus-leaf-tea products with desirable flavor and health benefits.